Soph's plant kitchen : delicious high protein recipes to fuel you for life - Waplington, Sophie (Yellow Kite, 2025)
A qualified personal trainer with a passion for food, Sophie knows the vital role diet - and particularly eating plenty of protein and fibre - plays in nurturing a healthy body and a happy mind. Her recipes have been described as 'plant-based perfection'. Sophie also knows how busy everyone is so in her first book she shows how easy it is to eat delicious protein and fibre packed meals without spending hours in the kitchen. With over 100 recipes covering everything from meal-prep lunches to comforting classics and high protein treats, including: Breakfast Burrito Easy Ginger, Miso and Lime Noodle Salad Satay Chickpea and Quinoa Creamy Courgette and Butterbean Bowl Falafel Pot Pie, Tofu Banoffee Pie Slices. And to make it even easier to hit your goals each recipe contains grams of protein and fibre per portion.